Effectiveness of RGEC Banks Soundness Level, Exchange Rate and Interest Rate in Predicting Potential Bank Bankruptcy - Satriya Dharma Mukti; Tri Gunarsih (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study examines the RGEC-based bank soundness level, Exchange Rate, and Interest Rate in predicting potential banking bankruptcy. The sample in this study consists of 152 data obtained from 38 banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. The results of this study show that Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR) and Self-Assessment Good Corporate Governance (GCG) have a significant positive effect on the potential for bankruptcy, on the other Return on Asset (ROA) have a negative and significant impact on the potential for bankruptcy. Furthermore, the Capital Adequacy Ratio (CAR), Exchange Rate, and Interest Rate have no effect on the potential for bankruptcy. The study results show that four indicators, out of the five indicators of RGEC banks' soundness level, are effective in predicting potential bankruptcy. These results show that if bank management wants to predict and anticipate bankruptcy based on its health level, it can be considered to see and maintain NPL, LDR, GCG self-assessments, and ROA.